The potential of oxygen and nitrogen species-regulating drug delivery systems in medicine - Sołtan, Michał; Bartusik-Aebisher, Dorota; Aebisher, David (Frontiers in Bioengineering and Biotechnology, 2022)
The focus of this review is to present most significant reactive oxygen/nitrogen species (ROS/RNS, RONS) responsive for treatment in biomaterials. Summary of main pathways of ROS production and main pathways of RNS production are shown herein. Although the physiological and pathological roles of RONS have been known for at least two past decades, the potential of their control in management of disease went unappreciated. Recently, advances in the field of biochemical engineering and materials science have been made to develop RONS-responsive biomaterials for biomedical applications, which aim to control and change levels of reactive species in tissue microenvironments. These materials utilize polymers, inorganic nanoparticles (NPs), or organic-inorganic hybrids. Thus, biomaterials like hydrogels have been developed to promote tissue regeneration, by actively scavenging and reducing RONS levels. Their promising utility comes from thermo- and RONS-sensitivity, stability as a delivery-medium, ease for incorporation of other materials and facility for injection. Their particular attractiveness is attributed to the drug release being realized in targeted tissues and cells with elevated RONS levels, which leads to enhanced treatment outcome and reduced adverse effects. The mechanism of their action depends on the functional groups employed and their response to oxidation, and may be based on solubility change or cleavage of chemical bonds. This study is a review of articles in English from the databases PubMed and Web of Science retrieved by applying the search terms “Oxygen Species, Nitrogen Species and biomaterials” from 1996–2021.